Effects of multiple pulmonary aspirations of enteral solutions on lung tissue damage - YILDIZELİ, BEDRETTİN; UMUROĞLU, TÜMAY (CHURCHILL LIVINGSTONE, 2006)
Background Et aim: The aim of this study was to compare the pulmonary histopathologic effects of enteral solutions with various lipid content, after multiple aspirations in rats. Methods: Thirty Wistar albino rats were randomly assigned to one of three groups (n = 10). Salinesolution (0.9%) (group C, control), Impact (lipid content, 28g/l; group I), Pulmocare (lipid content, 93.3g/l; group P) were injected into the lung through the trachea, in a volume of 0.8 ml/kg. The aspiration procedure was performed three times in total, in every 2 days. After seven days from the first aspiration, rats were killed, and lungs were examined for histopathologic examination. Results: Alveolar histiocytes were statistically higher in left lungs of the group I than the left ones of the control group(P < 0.05). Lipid-laden alveolar macrophages were significantly higher in left lungs of groups I and, P than left lungs of the control group (P < 0.05). Conclusion: Lung tissue damage occuring after multiple pulmonary aspirations of Impact and Pulmocare, is histopathotogically similar to each other, and is in the form of lipoid pneumonia. In cases of multiple pulmonary aspirations, volume of the aspirate and chronicicity of the aspiration took like major impact factors rather than the amount of the lipid. (c) 2005 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: acute lung injury; enteral formulas; lipoid pneumonia; LIPOID PNEUMONIA; CHILDREN; FEEDINGS; GUT